Вплив змiн дефектних станiв на властивостi фотокатода Si–Gd–O - Mel’nyk, P. V.; Nakhodkin, M. G.; Fedorchenko, M. I. (Publishing house "Academperiodika", 2018)
Changes in the electronic and emission properties of a photocathode on the basis of a multilayered structure of oxidized Gd atoms (probably, Gd2O3) on the Si(100) substrate after the deposition of additional layers of Gd atoms onto its surface and the bombardment with Ar ions have been studied by the methods of photoelectron (ℎv = 2.3÷10.2 eV) and Auger electron spectroscopies. The modifications of photocathode properties are found to depend on the defectness of the near-surface photocathode layer, being a result of the change in the concentration of localized electron states located in the energy gap of Gd2O3. It is shown that the bombardment of a Si–Gd–O cathode with Ar ions and its exposition to atomic hydrogen can be used to control its spectral and emission characteristics. A possibility to use the energy diagram proposed by us for the photocathode to qualitatively analyze its properties is confirmed.